WOx‐Surface Decorated PtNi@Pt Dendritic Nanowires as Efficient pH‐Universal Hydrogen Evolution Electrocatalysts. Issue 3 (30th November 2020) - Zhang, Weiyu; Huang, Bolong; Wang, Kai; Yang, Wenxiu; Lv, Fan; Li, Na; Chao, Yuguang; Zhou, Peng; Yang, Yong; Li, Yingjie; Zhou, Jinhui; Zhang, Wenshu; et al.
Abstract: The hydrogen evolution reaction (HER) is a pivotal element of electrochemical water splitting which is able to produce clean hydrogen as an alternative to fossil fuel. Developing efficient Pt‐based electrocatalysts for the HER to work at all pHs is highly desirable, however, still a significant challenge, especially in alkaline conditions due to sluggish water dissociation and OHad transfer. Here, a new strategy for making a class of amorphous WO x ‐surface decorated PtNi@Pt dendritic nanowires (WO x ‐PtNi@Pt DNWs) to achieve highly efficient pH‐universal HER electrocatalysis is reported. The as‐made WO x ‐PtNi@Pt DNWs display superior HER performance with the overpotentials of 24, 5, and 22 mV in 0.1 m KOH, 0.1 m HClO4, and 0.5 m phosphate‐buffered saline, respectively, at a current density of 10 mA cm −2 . The mass activity of WO x ‐PtNi@Pt DNWs in alkaline conditions is 3.3 mA μgPt −1 at an overpotential of 70 mV, among the best in all the reported materials. Theoretical calculations confirm the introduction of WO x to the PtNi DNWs plays a pivotal role in promoting the efficient electron transfer for the alkaline and acidic HER. The activation of the PtNi region within the PtNiWO interface is achieved by the WO x induced strain effect, which guarantees the superior performance in the HER. Abstract : Novel amorphous WO x ‐surface decorated PtNi@Pt dendritic nanowires are successfully synthesized by a one‐pot chemical approach. This electrocatalyst exhibits excellent pH‐universal electrocatalytic performance for the hydrogen evolution reaction, which is attributed to the unique PtNiWO interface.